Selected universal processes leading to changes in world’s languages - Kida, Ireneusz (Slavia Centralis, 2021)
The article discusses various processes,such as umlaut, vowel harmony, lenition and grammaticalisation, which lead to language change. These processes seem to be universal and they can be found in numerous languages of the world. Aspects of the following languages are going to be discussed here: English, German, Swedish, Latin, Spanish, French, Arabic, Polish, Serbian, Macedonian, Romanian, Greek, Finnish and Tok Pisin.
Keywords: language change; umlaut; vowel harmony; lenition; grammaticalisation